The Prehistoric Maritime Frontier of Southeast China Indigenous Bai Yue and Their Oceanic Dispersal - Wu, Chunming (The Archaeology of Asia-Pacific Navigation, 2021)
This open access book presents multidisciplinary research on the cultural history, ethnic connectivity, and oceanic transportation of the ancient Indigenous Bai Yue (百越) in the prehistoric maritime region of southeast China and southeast Asia. In this maritime Frontier of China, historical documents demonstrate the development of the "barbarian" Bai Yue and Island Yi (岛夷) and their cultural interaction with the northern Huaxia (华夏) in early Chinese civilization within the geopolitical order of the "Central State-Four Peripheries Barbarians-Four Seas". Archaeological typologies of the prehistoric remains reveal a unique cultural tradition dominantly originating from the local Paleolithic age and continuing to early Neolithization across this border region. Further analysis of material culture from the Neolithic to the Early Iron Age proves the stability and resilience of the indigenous cultures even with the migratory expansion of Huaxia and Han (汉) from north to south. Ethnographical investigations of aboriginal heritage highlight their native cultural context, seafaring technology and navigation techniques, and their interaction with Austronesian and other foreign maritime ethnicities. In a word, this manuscript presents a new perspective on the unique cultural landscape of indigenous ethnicities in southeast China with thousands of years' stable tradition, a remarkable maritime orientation and overseas cultural hybridization in the coastal region of southeast China.